Financial Sector Assessment : Fiji - World Bank (Washington, DC, 2012)
The financial sector in Fiji is generally sound but has concentrated too heavily on domestic exposures producing a lack of risk diversification. This concentration is an increasing vulnerability, as foreign currency earnings become more dependent on tourism and remittances from workers overseas. Fiji has a financially strong and highly profitable banking sector, good supervision and laws, and a high degree of long-term contractual savings through the insurance and pension sectors. The major distortion arises, however, from the Fiji National Provident Fund (FNPF), which itself accounts for about 40 percent of financial system assets. This paper takes a close look at Fiji's financial sector as it relates to the following: macroeconomic environment and risk; monetary policy, the financial sector stability and performance of the banking, insurance and Provident national fund; the regulatory framework; access to finance; payment systems; and anti laundering and terrorism. The paper also gives and overall assessment and key recommendations.